Mining, heterologous expression, purification, antibactericidal mechanism, and application of bacteriocins: A review. Issue 1 (29th October 2020) - Cui, Yanlong; Luo, Lingli; Wang, Xin; Lu, Yingying; Yi, Yanglei; Shan, Yuanyuan; Liu, Bianfang; Zhou, Yuan; Lü, Xin
Abstract: Bacteriocins are generally considered as low‐molecular‐weight ribosomal peptides or proteins synthesized by G + and G − bacteria that inhibit or kill other related or unrelated microorganisms. However, low yield is an important factor restricting the application of bacteriocins. This paper reviews mining methods, heterologous expression in different systems, the purification technologies applied to bacteriocins, and identification methods, as well as the antibacterial mechanism and applications in three different food systems. Bioinformatics improves the efficiency of bacteriocins mining. Bacteriocins can be heterologously expressed in different expression systems (e.g., Escherichia coli, Lactobacillus, and yeast). Ammonium sulfate precipitation, dialysis membrane, pH‐mediated cell adsorption/desorption, solvent extraction, macroporous resin column, and chromatography are always used as purification methods for bacteriocins. The bacteriocins are identified through electrophoresis and mass spectrum. Cell envelope (e.g., cell permeabilization and pore formation) and inhibition of gene expression are common antibacterial mechanisms of bacteriocins. Bacteriocins can be added to protect meat products (e.g., beef and sausages), dairy products (e.g., cheese, milk, and yogurt), and vegetables and fruits (e.g., salad, apple juice, and soybean sprouts). The future research directions are also prospected.